The methods of probability estimation of the aircraft engines parts wear - Кучеренко, В. О. (Proceedings of National Aviation University (archive), 2021)
There was obtained the average of distribution probability estimation of the aircraft engines parts wear that has the decisive importance for prediction of the wear process probability and the optimal terms of the routine repair work directed to increase of the engines parts wear resistant.